Pengaruh Kepuasan Kerja Dan Stres Kerja Terhadap Kinerja Karyawan Pada PT Xinghao Technology Tangerang Selatan - Aura Aleyda Setiadi; Nurdinni Tilova (LAP4B, 2025)
The research in this thesis aims to analyze the influence of Job Satisfaction and Job Stress on Employee Performance at PT Xinghao Technology, South Tangerang. The method used in this study is a saturated sample with a population of 110 people, where all members of the population are used as respondents. Data collection techniques are carried out through observation and questionnaire distribution. The data obtained are analyzed using validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, correlation coefficients, determination coefficients, and hypothesis tests (t-test and F-test). The results show that Job Satisfaction has a significant effect on employee performance with a determination coefficient value of 49.7% and the hypothesis test obtained t count > t table (5.958 > 1.982). Job stress does not significantly influence employee performance, with a determination coefficient value of 18.8% and a hypothesis test of t count < t table (-1.989 < 1.982). Simultaneously, these two variables influence Employee Performance (F count > F table) with a regression equation of Y = 18.972 + 0.532X1 + 0.006X1 and a determination coefficient value of 49.7% indicating that 50.3% is influenced by other factors. This means that if there is an increase in the variables of Job Satisfaction and Job Stress, it will affect employee performance. The variable that has the most dominant influence on employee performance is the job satisfaction variable of 49.7%. The hypothesis test is obtained from the value of F count > F table (17.598 > 3.08). So it can be concluded that Job Satisfaction (X1) and Job Stress (X2) simultaneously have a significant effect on employee performance